The Distribution Features of Polysaccharides and Lipids in the Development of Tomato Anthers - Zhu Yun; Tian Huiqiao (Horticultural Plant Journal, 2015)
The regulation of nutrient transportation and transformation in developing anthers is very complex. We analyzed the distribution and features of polysaccharides and lipids in the developing anthers of tomatoes using histochemical methods. Some starches appeared in the connective somatic tissue of anthers during the sporogenous cell stage. Before meiosis of the microspore mother cell, a thick polysaccharide callose wall was formed, accompanied by a reduction in the connective tissue starches. During the tetrad stage after meiosis, the polysaccharide material in the anther did not change. At the early microspore stage, the starches in the connective cells again increased, and polysaccharide material appeared in the partial intine of pollen. At the late microspore stage, a large vacuole formed that did not contain lipids or starches, and only the pollen wall contained red polysaccharides. At this stage, the connective somatic cell starch amounts decreased, and the tapetal cells changed shape and degenerated. After microspore division, abundant lipids appeared in the bicellular pollen, and starches accumulated following pollen development. As the anthers matured, many lipids and some starches accumulated in the epidermal cells. Nutrient metabolism within the tomato pollen characteristically accumulated lipids first and then starches, while the mature pollen accumulated starches and lipids simultaneously. This characteristic pattern of nutrient metabolism in tomato pollen shows species specificity among plants.